The Construction of Librarians’ Professional Identities: A Discourse Analysis - Hicks, Deborah (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2016)
Professional identities shape the way professions interact with their clients and society. As librarians are service-oriented professionals, a discursively informed understanding of identity can provide a new way to examine identity and expose the ways it impacts and informs how librarians interact with their clients and society at large. L’identité professionnelle détermine la façon qu’a une profession d’interagir avec sa clientèle et la société. Les bibliothécaires étant des professionnels dont la raison d’être est de rendre des services, saisir leur identité en s’appuyant sur la discursivité peut fournir une façon nouvelle d'examiner l'identité et d’exposer comment les bibliothécaires interagissent avec leurs clients et la société en général. *** Awarded the 2014 Student-to-CAIS Award ***